النفي في سورة آل عمران دراسة نصية حجاجية - بن بداري, كنيوة, وردة صفاء (Univesity of El-Oued, 2022)
ناولت هذه الدراسة "النّفي في سورة آل عمران – دراسة نصية حجاجية-"،بحيث سلطت الضوء على الوظيفة النَّصية التي تضطلع بها أدوات النفي المحيلة في نماذج القرآنية وسلطت الضوء على الوظيفة الحجاجيَّة التي تضطلع بها أدوات النَّافية الصريحة الحجاجيَّة في نماذج القرآنية، وتهدف هذه الدراسة الى إثبات فرضتين النصية النفي في سورة آل عمران،وحجاجية النفي في سورة آل عمران، حيث توصلت الدراسة إلى أنَّ النفي آلية رابطة بين المقاطع النَّصية في النص القرآني لتظهر النصوص بنية ملتحمة ودلالة موحدة ،وآلية إقناعية يستخدمها المحاجج لتبليغ مقاصده عن طريق نقض فكرة وأدحضها،والإقناع بالوقف المراد قصد التأثير في المتلقي وتوجيهه إلى النتيجة المقصودة ،وللانتقال من التأثير الفكري إلى الإنجازي في الواقع. . Abstract function of the referential negation tools in the Qur'anic models، and sheds light on the argumentative function carried out by the explicit negation tools in the Qur'anic models، and this study aims to Proving the two textual hypotheses of negation in Surat Al Imran، and Hajjajiyah of denial in Surat Al Imran، where the study concluded that negation is a linking mechanism between the textual passages in the Qur’anic text so that the texts appear This study dealt with "the negation in Surat Al Imran - textually and pilgrimage"، as it sheds light on the textual with a cohesive structure and unified significance، and a persuasive mechanism used by the argumentative to communicate his intentions by refuting and refuting an idea، and persuasion By endowment intended to influence the recipient and direct him to the intended result، and to move from intellectual influence to achievement in reality.
Keywords: نصيَّة النفي ،حجاجيَّة النَّفي ،الإحالة الزمنية، أدوات النفي ،المقطع النَّصي، الخطاب القرآني، الإقناع